Fashion resale as a strategy for the circular economy - Kochová, Rebeka; Vlčková, Jana; De Castro, Tereza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The main objective of this diploma thesis is to examine the transition from a linear to a circular economy in the global fashion industry, with a specific focus on the resale business model. The fashion industry is one of the most wasteful and resource-intensive sectors, and resale is increasingly viewed as a way to minimise its footprint on the environment. Platforms like Vinted and ThredUp demonstrate that non-traditional business models can succeed at driving growth for resale, with Vinted even becoming profitable. However, the analysis also discovers that the sustainability of resale depends on repeated use of clothes and the replacement of new purchases. Challenges such as market over-saturation with low-quality fast fashion, negative perceptions of second-hand clothing and the environmental impact of exports to developing countries remain key barriers. Nevertheless, the resale market offers strong economic and environmental potential provided that all stakeholders take active steps to address these challenges and support its development.
Vedoucí práce: Jana Vlčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses